Formate hydrogenlyase in the hyperthermophilic archaeon, Thermococcus litoralis - Takács, Mária (BioMed Central, 2008)
BACKGROUND: Thermococcus litoralis is a heterotrophic facultative sulfur dependent hyperthermophilic Archaeon, which was isolated from a shallow submarine thermal spring. It has been successfully used in a two-stage fermentation system, where various keratinaceous wastes of animal origin were converted to biohydrogen. In this system T. litoralis performed better than its close relative, P. furiosus. Therefore, new alternative enzymes involved in peptide and hydrogen metabolism were assumed in T. litoralis. RESULTS: An about 10.5 kb long genomic region was isolated and sequenced from Thermococcus litoralis. In silico analysis revealed that the region contained a putative operon consisting of eight genes: the fdhAB genes coding for a formate dehydrogenase and the mhyCDEFGH genes encoding a [NiFe] hydrogenase belonging to the group of the H(2)-evolving, energy-conserving, membrane-bound hydrogenases. Reverse transcription linked quantitative Real-Time PCR and Western blotting experiments showed that the expression of the fdh-mhy operon was up-regulated during fermentative growth on peptides and down-regulated in cells cultivated in the presence of sulfur. Immunoblotting and protein separation experiments performed on cell fractions indicated that the formate dehydrogenase part of the complex is associated to the membrane-bound [NiFe] hydrogenase. CONCLUSION: The formate dehydrogenase together with the membrane-bound [NiFe] hydrogenase formed a formate hydrogenlyase (formate dehydrogenase coupled hydrogenase, FDH-MHY) complex. The expression data suggested that its physiological role is linked to the removal of formate likely generated during anaerobic peptide fermentation.